Tetramethylpyrazine Alleviates Endothelial Glycocalyx Degradation and Promotes Glycocalyx Restoration via TLR4/NF-κB/HPSE1 Signaling Pathway During Inflammation - Lei, Jin; Xiang, Peng; Zeng, Shengmei; Chen, Le; Zhang, Lei; Yuan, Zhiyi; Zhang, Jun; Wang, Tingting; Yu, Ruihong; Zhang, Wanping; Ibrahim, Issa Issoufou; Ma, Limei; et al. (Frontiers in Pharmacology, 2022)
Disruption of vascular endothelial glycocalyx during inflammation is causally related to the microvascular endothelial dysfunction, a characteristic of endothelial injuries induced and further aggravated vascular injury diseases, such as atherosclerosis (AS). Tetramethylpyrazine (TMP), a Chinese traditional herbal extraction and widely used in the treatment of cardiovascular diseases, could attenuate vascular endothelial injuries, but the underlying mechanism remains incomprehensive. Here, we thoroughly investigated the molecular mechanism of TMP on vascular endothelial glycocalyx in the LPS-induced inflammatory model both in vitro and in vivo. Results showed that pretreatment with TMP significantly inhibited glycocalyx degradation and monocytes adhesion to endothelial process. Moreover, TMP pretreatment inhibited the expression of HPSE1 (a major degrading enzyme of endothelial glycocalyx), Toll-like receptor 4 (TLR4), and the translocation of nuclear factor kappa B p65 (NF-κB p65), which indicated that TMP might suppress glycocalyx degradation through TLR4/NF-κB/HPSE1 signaling pathway. Moreover, TLR4 siRNA, NF-κB inhibitor and HPSE1 overexpression analysis confirmed TMP’s protection on endothelial glycocalyx injury, which further contributed to the monocyte-endothelial adhesion process. Taken together, our results enriched the occurrence molecular mechanism of glycocalyx shedding, and regulation molecular mechanism of TMP in protecting integrity of the glycocalyx structure during inflammation. As TMP is currently used in clinical applications, it may be considered as a novel strategy against atherosclerosis, through its ability to protect endothelial glycocalyx.